Coopetitive cannibalization on ICT channel: empirical evidence from the expansion of online-based games to mobile platform - Choi, Hyeri; Park, Min Jae (Technology Analysis and Strategic Management, 2025)
This study aims to analyze the occurrence and extent of the cannibalisation phenomenon in the game industry’s channel expansion. The process of rising and declining between PC-based massively multiplayer online role-playing games (MMORPG) and mobile games in a competitive relationship is explained through the interaction between the two channels. Using the Lotka-Volterra competition models, this study estimates the parameters of channel interaction and assesses the competitive dynamics between the online and mobile channels. The results indicate that introducing a mobile platform can extend the life cycle of the online channel despite initial cannibalisation effects. They highlight the strategic management of channel expansion and the necessity for firms to navigate the complexities of technological innovation and cannibalisation.
Keywords: cannibalization; Coopetition; game industry; Lotka-Volterra model